Buletin Peternakan : Respon Pemberian Tepung Daun Kelor (Moringa oleifera) pada Pakan Ayam Petelur terhadap Penampilan Produksi dan Kualitas Telur - Edi Wahyu Satria, Osfar Sjofjan, Irfan Hadji Djunaidi (Peternakan UGM, 2016)
The purpose of this study was to determine the effect of Moringa leaf meal (Moringa oleifera) in feed on production performance and egg quality of laying hens. The materials used 120 laying hens of Isa Brown breed in 38 to 42 weeks age.